2022
DOI: 10.1002/fsn3.2940
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol yeast T‐2 improves the postharvest disease resistance of grape by stimulation of the antioxidant system

Abstract: As independent individuals, the postharvest grapefruits will undergo a series of physiological and biochemical changes when dealing with pathogenic bacteria. Reactive oxygen species (ROS) are reactive molecules and free radicals produced by oxygen molecules, and its production is an initial and universal response of plant to pathogen attack (Mittler, 2002;. Uncontrolled overproduction of ROS disrupts normal metabolism by oxidizing proteins and lipids affecting the integrity of cell membranes and inactivating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…Interestingly, the Trichoderma application also helped to retain the berry freshness for a longer duration. Wu et al, (2022) also reported that the bio-control yeast Metschnikowia Pulcherrima T-2 not only reduced Botrytis cinerea infection on grape berries but also reduced the browning rate and shedding rate of berries during storage. The increased activities of antioxidant enzymes such as peroxidase, catalase, and phenylalanin ammonia-lyase in grapes treated with T-2 during storage time were found responsible for the reduced oxidative damage.…”
Section: Microbes For Control Of Postharvest Decaymentioning
confidence: 91%
“…Interestingly, the Trichoderma application also helped to retain the berry freshness for a longer duration. Wu et al, (2022) also reported that the bio-control yeast Metschnikowia Pulcherrima T-2 not only reduced Botrytis cinerea infection on grape berries but also reduced the browning rate and shedding rate of berries during storage. The increased activities of antioxidant enzymes such as peroxidase, catalase, and phenylalanin ammonia-lyase in grapes treated with T-2 during storage time were found responsible for the reduced oxidative damage.…”
Section: Microbes For Control Of Postharvest Decaymentioning
confidence: 91%
“…Three biological replicates were determined for each sample, 10 tomato fruits were used as one biological replicate. The determination of tomato fruit weight loss was described previously ( Wu et al., 2022 ). Methods for TSS, TA, Vc content were also described previously ( Sdiri et al., 2012 ).…”
Section: Methodsmentioning
confidence: 99%